Psychopathology in Severely Obese Women from a Canadian Bariatric Setting. Issue 2 (20th August 2014) - Strimas, Rachel; Dionne, Michelle M.; Cassin, Stephanie E.; Wnuk, Susan; Taube-Schiff, Marlene; Sockalingam, Sanjeev
Abstract : Purpose: Evidence suggests high rates of psychiatric disorders in bariatric surgery candidates (e.g., Mitchell et al., 2012), although no rigorous studies have examined the prevalence in a Canadian sample. Improved understanding of the prevalence of psychopathology among female patients is an important area of study, as females comprise approximately 80% of surgical candidates (Martin et al., 2010; Padwal, 2005). This study assessed the prevalence of Axis I disorders and associations with quality of life in a Canadian sample of female bariatric surgery candidates. Design/methodology/approach: Female patients (N = 257) were assessed using a structured psychodiagnostic interview and completed a health-related quality of life questionnaire. Findings: Results indicated that 57.2% of patients met DSM-IV-TR criteria for a lifetime psychiatric disorder and 18.3% met criteria for a current psychiatric disorder. Major depressive disorder was the most common lifetime psychiatric disorder (35.0%) and binge eating disorder was the most prevalent current psychiatric disorder (6.6%). Patients scored significantly lower than Canadian population norms on all domains of the SF-36 (all ps < .001). Patients with a current Axis I disorder also reported significantly worse functioning on four mental health domains and one physical health domain (p's < .01) compared to patients without a current Axis I disorder. Originality/value: Results confirm high rates of psychiatric disorders in Canadian female bariatric surgery candidates and provide evidence for associated functional health impairment. Further study is needed to elucidate how pre-operative psychopathology may impact female patients' post-operative outcomes.